Response surface optimization for cadmium biosorption onto the pre-treated biomass of red algae Digenia simplex as a sustainable indigenous biosorbent - Sedky H.A. Hassan; Maryam M. Alomran; Nada I.A. Alsugiran; Mostafa Koutb; Hassan Ahmed; Mustafa A. Fawzy (PeerJ)
Background Cadmium pollution from industrial effluent can cause major health concerns, so it must be removed from wastewater prior to disposal. The objective of this study was to remove cadmium (Cd2+) from aquatic environments using red macroalgae Digenia simplex pretreated with calcium chloride (CaCl2) (DSC). Methods Batch adsorption studies were carried out to evaluate the individual impacts of adsorbent-metal contact time, cadmium concentration, and temperature on the cadmium removal efficiency and biosorption capacity. The Box-Benhken experimental design of response surface methodology was also used to investigate the relationship between different factors (pH, Cd2+ concentration and algal dose) and the cadmium removal efficiency of pretreated D. simplex. Results The highest removal efficiency of 97.27% was achieved by combining different optimal parameters, including pH 5.78, initial Cd2+ concentration of 24.79 mg/L, and adsorbent dosage of 6.13 g/L. Moreover, cadmium removal from agricultural wastewater samples by pretreated D. simplex was evaluated under the optimal conditions, and the removal rate excessed 97%. Kinetic and isotherm investigations showed that the pseudo-second-order, Freundlich, Langmuir, and Dubinin–Radushkevich models of cadmium biosorption on pretreated algal biomass correlated well with the experimental biosorption data, implying that the biosorption of Cd2+ is a homogeneous monolayer and multilayer chemisorption process. The equilibrium isotherm data indicated that the biosorption capacity of the biosorbent was 11.16 mg/g as determined by the Langmuir model. Furthermore, the biosorption process was evaluated as an endothermic process with entropy and enthalpy values of 0.134 kJ/mol K and 38.01 kJ/mol, respectively. The functional groups, surface morphology, and elemental composition of the algal biomass were investigated, revealing the porous nature of the cell surface and the abundance of functional groups responsible for the Cd2+ biosorption process. These results suggest that DSC biomass can be used as a biosorbent for the effective removal of Cd2+ ions from effluent due to its availability and strong biosorption capability.